Gemini mid-IR polarimetry of NGC 1068: Polarized structures around the nucleus - Packham, C; Young, S; Fisher, S; Volk, K; Mason, R; Hough, J; Roche, P; Elitzur, M; Radomski, J; Perlman, E (2007)
We present diffraction-limited, 10 μm imaging polarimetry data for the central regions of the archetypal Seyfert active galactic nucleus NGC 1068. The position angle of polarization is consistent with three dominant polarizing mechanisms. We identify three distinct regions of polarization: (1) north of the nucleus, arising from aligned dust in the narrow emission line region, (2) south, east, and west of the nucleus, consistent with dust being channeled toward the central engine, and (3) a central minimum of polarization consistent with a compact (≤22 pc) torus. These observations provide continuity between the geometrically and optically thick torus and the host galaxy's nuclear environments. These images represent the first published mid-IR polarimetry from an 8 m-class telescope and illustrate the potential of such observations. © 2007. The American Astronomical Society. All rights reserved.